1966
DOI: 10.5006/0010-9312-22.4.107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cr Content On Pitting Behavior of Fe-Cr Alloys

Abstract: Immersion and applied current studies are used to investigate the pitting behavior of binary Fe-Cr alloys formed both by conventional melting techniques and by diffusion of chromium into mild steel (chromizing). Experiments on both sets of materials show that a chromium content of 28–30 percent is critical for elimination of room-temperature pitting corrosion. It is proposed that chromium acts to improve the pitting resistance of Fe-Cr alloys by stabilizing passivity, thus reducing pit initiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1969
1969
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Not all investigators are convinced of the utility of such a concept, (79) although the basis of available evidence suggests that it has some engineering value. (80) 9.…”
Section: Pitting In the Passive Potential Rangementioning
confidence: 99%
See 1 more Smart Citation
“…Not all investigators are convinced of the utility of such a concept, (79) although the basis of available evidence suggests that it has some engineering value. (80) 9.…”
Section: Pitting In the Passive Potential Rangementioning
confidence: 99%
“…These quantities are defined in Figure 95, which also suggests that corrosion fatigue and stress corrosion cracking processes may be a part ofthe same continuum. Detailed aspects of corrosion fatigue have been summarized in a recently published volume,u 79) As was necessary in considering the stress corrosion cracking of metals, distinguishing between initiation and propagation processes is also important in corrosion fatigue. The initiation process is usually defined by testing smooth specimens and determining the number of cycles to failure.…”
Section: Relationship Between Environmental Effects On Static Loadingmentioning
confidence: 99%
“…have been usefully applied to the study of pitting corrosion (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In presence of anions enabling pitting corrosion, the potential does not reach oxygen evolution, and the current increases steadily at lower potential, dependent on a number of factors (6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…In presence of anions enabling pitting corrosion, the potential does not reach oxygen evolution, and the current increases steadily at lower potential, dependent on a number of factors (6)(7)(8)(9)(10)(11)(12)(13). This increase in current does not occur directly after the addition of the aggressive ion, but a certain time elapses.…”
Section: Introductionmentioning
confidence: 99%
“…Steigerward [17] reported that pitting corrosion in the immersion tests took place at much lower potentials than the pitting potential determined by the electrochemical technique. He measured the corrosion potential after only 65 hours of exposure of Fe-Cr alloys to a 10 percent FeC136H 20 solution.…”
Section: Interpretation Of Electrochemically and Chemically Investigamentioning
confidence: 99%